Adopting abundant seawater as green chemical activators for preparing high surface area biochar. (February 2023) - Wang, TsingHai; Lin, Yu-Ching; Hung, Ci-Jing; Liao, Yasi; Xu, Ruo-Xin
Abstract: Equipping the agricultural waste with new functionality through a green route echoes the spirit of the circular economy by minimizing the environmental impact. We propose herein to adopt abundant seawater as the green chemical activation reagent to prepare high surface area biochar. By this arrangement, the gasification of seawater Na + ions in the matrix of the beer dregs in the pyrolysis process leaves the porous biochar with a high surface area > 380 m 2 /g at 800 °C. Pyrolysis temperature plays the determining factor in developing the surface area due to the limited amount of seawater activators compared to the amount used in the conventional chemical activation. By contrast, seawater minerals are mainly responsible for the surface chemistry of biochar. Lastly, carbonization pretreatment is essential to facilitate seawater sodium ions diffusing into the matrix. Graphic abstract: Unlabelled Image Highlights: Seawater could function as a green chemical activator for preparing biochar. Activation using seawater leaves the biochar with a surface area >380 m 2 /g. Carbonization pretreatment facilitates seawater sodium diffusing into the matrix. Precipitation of seawater Mg 2+ and Ca 2+ reduces biochar's surface area.